2016
DOI: 10.1111/jmwh.12396
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Task Shifting to Increase Access to Maternal and Infant Health Interventions: A Case Study of Midwives for Haiti

Abstract: The shortage of health workers worldwide has been identified as a barrier to achieving targeted health goals. Task shifting has been recommended by the World Health Organization to increase access to trained and skilled birth attendants. One example of task shifting is the use of cadres of health care workers, such as nurses and auxiliary nurse-midwives, who can successfully deliver skilled care to women and infants in low-resource areas where women would otherwise lack access to critical health interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Indeed, Calitri et al reported that patients managed by a nurse telephone triage consultation in general practice showed low levels of satisfaction . Conflicting evidence was found that trained nurses and midwives can successfully deliver skilled health care to women and infants and manage their complications as effectively, safely and on time as obstetricians . Trained nurse healthcare professionals may provide prenatal and postnatal healthcare management and impact future maternal and child well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Calitri et al reported that patients managed by a nurse telephone triage consultation in general practice showed low levels of satisfaction . Conflicting evidence was found that trained nurses and midwives can successfully deliver skilled health care to women and infants and manage their complications as effectively, safely and on time as obstetricians . Trained nurse healthcare professionals may provide prenatal and postnatal healthcare management and impact future maternal and child well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of shifting tasks is to share the care from one level of caregiver to another to increase access to care. By training nurses and auxiliary nurse-midwives and their collaboration successfully, skilled care is delivered to women and infants in low-resource areas in Haiti [31]. Previous study on obstetrical nurses’ intentions toward collaborating with midwives in Ontario, Canada, showed that the nurses had positive intentions to collaborate with midwives, however, behaving collaboratively needed to be supported by indicating positive outcomes of collaboration and increasing inter-professional interaction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Haiti has a critical need to increase prenatal care access. One group that is attempting to meet this need is Midwives for Haiti, a nonprofit organization that aims to reduce maternal and infant mortality …”
Section: Setting: Maternal Health In Haitimentioning
confidence: 99%
“…Midwives for Haiti has increased access to care in rural areas by training skilled birth attendants and matwòns and performing over 500 prenatal examinations each month via mobile clinics in rural villages . To build upon these efforts, in 2014, Midwives for Haiti stakeholders sought to maximize utilization of resources by adapting an evidence‐based model of group prenatal care that could promote greater patient engagement, personal empowerment, and improved birth outcomes.…”
Section: Processmentioning
confidence: 99%
See 1 more Smart Citation